#### Answer

$3\rightarrow A$

#### Work Step by Step

$x^{3}+y^{3}=\left( x+y\right) \left( x^{2}-xy+y^{2}\right) \Rightarrow 3\rightarrow A$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$3\rightarrow A$

$x^{3}+y^{3}=\left( x+y\right) \left( x^{2}-xy+y^{2}\right) \Rightarrow 3\rightarrow A$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.